Perceived daily sleep need and sleep debt in adolescents: associations with daily affect over school and vacation periods. Issue 12 (29th July 2021) - Shen, Lin; Wiley, Joshua F; Bei, Bei
Abstract: Study Objectives: To describe trajectories of daily perceived sleep need and sleep debt, and examine if cumulative perceived sleep debt predicts next-day affect. Methods: Daily sleep and affect were measured over two school weeks and two vacation weeks ( N = 205, 54.1% females, M ± SD age = 16.9 ± 0.87 years). Each day, participants wore actigraphs and self-reported the amount of sleep needed to function well the next day (i.e. perceived sleep need), sleep duration, and high- and low-arousal positive and negative affect (PA, NA). Cumulative perceived sleep debt was calculated as the weighted average of the difference between perceived sleep need and sleep duration over the past 3 days. Cross-lagged, multilevel models were used to test cumulative sleep debt as a predictor of next-day affect. Lagged affect, day of the week, study day, and sociodemographics were controlled. Results: Perceived sleep need was lower early in the school week, before increasing in the second half of the week. Adolescents accumulated perceived sleep debt across school days and reduced it during weekends. On weekends and vacations, adolescents self-reported meeting their sleep need, sleeping the amount, or more than the amount of sleep they perceived as needing. Higher cumulative actigraphy sleep debt predicted higher next-day high arousal NA; higher cumulative diary sleep debt predicted higher NA (regardless of arousal), and lower low arousal PA the following day. Conclusion: Adolescents experienced sustained, cumulative perceived sleep debt across school days. Weekends and vacations appeared to be opportunities for reducing sleep debt. Trajectories of sleep debt during vacation suggested recovery from school-related sleep restriction. Cumulative sleep debt was related to affect on a daily basis, highlighting the value of this measure for future research and interventions.